Performance-based assessment of long masonry structures - Cakır, Ferit (My University, 2022)
Performance-based assessment (PBA) has become an increasingly important concept for assessing the structural performance of existing structures today. This procedure aims primarily to determine structural damage subject to predetermined load effects and evaluate the state of the building based on the damage obtained. However, because of their complicated engineering characteristics and structural performance, it is very difficult to evaluate the performance of long masonry structures, such as aqueducts, castle ramparts and city walls. The PBA of long masonry structures is extremely challenging because there is no valid approach to assessing their performance. In this study, a practical evaluation method is developed to assess the structural performance of long structures and the seismic performance of Valens Aqueduct, which was constructed by the Roman Empire in Istanbul, is examined using this method.
Keywords: İnşaat Mühendisliği